Students’ Level of Understanding of Lithium-Ion Battery Concepts and Its Impact on Perceptions of Career Readiness - Muhammad Rafly Hibban; Wahid Munawar; Sriyono Sriyono (Journal of Creative Power and Ambition (JCPA), 2026)
The rapid growth of the electric vehicle industry in Indonesia has created an urgent demand for a technically competent workforce, particularly in mastering lithium-ion battery technology as the core component of electric vehicles. This study investigates the extent to which students' level of understanding of lithium-ion battery concepts influences their perceptions of career readiness in the electric vehicle industry. A quantitative approach with a correlational survey method was employed, involving 60 students as respondents. Data were collected through a questionnaire that had undergone validity and reliability testing, and subsequently analyzed using simple linear regression. The findings reveal that students' understanding of lithium-ion battery concepts has a significant effect on their career readiness perceptions, with a coefficient of determination of 52.5% and an F-value of 64.026 at a significance level of 0.000. These results suggest that the stronger a student's grasp of battery technology, the greater their confidence in entering the electric vehicle sector. This study provides empirical evidence that strengthening vocational and engineering education curricula, particularly in battery technology content, is a crucial step in preparing a competitive workforce for the continuously expanding electric vehicle industry.